CONFLITOS SOCIAIS E DIREITOS HUMANOS: ALTERNATIVAS ADEQUADAS DE TRATAMENTO E RESOLUÇÃO - Andrade, Thaís C. d.; Schunemann, Cristiane D.; Corrêa, Tobias D.; Spengler, Fabiana M. (Salão do Conhecimento, 2013)
Resumo